Mediating Role of Perceived Internal Status on the Relationship Between Perceived Psychological Empowerment and Loneliness at Workplace - Kanbur, Engin; Kanbur, Aysun (Business and Economics Research Journal, 2020)
The aim of this research is to examine whether or not perceived internal status has a mediating role on the relationship between perceived psychological empowerment and loneliness at workplace and its subdimensions. The sample of the research is constituted by 219 employees who are affiliated to the public institutions in the body of governorship of one of our province. For gathering the data, questionnaire technique was used. Correlation analysis and regression analysis were utilized for determining the relationships between variables of the research and testing the hypotheses. According to the findings, it can be seen that perceived psychological empowerment has positive relationship with perceived internal status and negative relationship with loneliness at workplace. It is determined in this research that perceived internal status has a full mediating role on the relationship between perceived psychological empowerment and loneliness at workplace. This mediating role shapes as partial mediating role on lack of social companionship side while there isn’t observed any mediating role on emotional deprivation side as subdimensions of loneliness at workplace.
Keywords: 10. No inequality